(untitled) (Tempo e Argumento, 2021)
This article presents and discusses the path that led to the organizational designs of the heavy division of the USSR and the USA at the start and at the end of the Cold War. It explains modern combined arms centred on the tank, and the central role of the army division (10,000-20,000 combatants) for the provision of the different types of troops required to have them when necessary. It then addresses the tank and mechanized corps of the USSR and the armored division in 1945, outlining how these led to the motor rifle and tank divisions of the USSR and the armored and mechanized divisions of the USA c. 1985, as proxy for 1991 to account to the turbulence at the end of the Cold War. It argues in conclusion for the continuity and prevalence of the issue of providing for combined arms centred on the tank in the division as the prime concern for the organizational design of ground forces to the present.